(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The emergence of memorial museums is rooted in wars throughout history. Examples include the Napoleonic Wars and World Wars. These memorial museums are built to honor individuals’ memories, educate younger generations about the consequences of wars, and immortalize victories. This article examines memorial complexes such as the "Valhalla Memorial," "People’s War Memorial," "Borodino Field," "Waterloo Memorial," and the "Liberty Statue.".